The Solvent Effects on the Energy Gap Between the $nπ^*$ State and $ππ^*$ State and Fluorescence of Benzoyleneurea (Journal of Atomic and Molecular Sciences, 2019)
Benzoyleneurea (BenzU), a fluorescent nucleobase analog, exhibits strong solvent dependentfluorescence intensity. With the increasing of the concentration of polar and protic solvents, BenzU exhibitsenhanced fluorescence. To understand the photophysical properties of BenzU, the energy gaps (ΔE) betweendark $nπ^*$ state and bright $ππ^*$ state of BenzU are calculated in several solvents. The solvent dielectricconstant and hydrogen bond between BenzU and protic solvent both have effects on ΔE. And thefluorescence quantum yields of BenzU are linear response to ΔE. Furthermore, we find that the morehydrogen bonds are formed between BenzU and protic solvent, the higher ΔE and fluorescence intensity areobtained.
Keywords: Fluorescence quantum yields; Hydrogen bonds; Solvent effects.